2021
DOI: 10.3389/fpsyt.2021.730448
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Korean Version of the Program for the Education and Enrichment of Relational Skills for Young Adults (PEERS®-YA-K) With Autism Spectrum Disorder: A Pilot Study

Abstract: Evidence-based social skills interventions for young adults are limited, despite social difficulties in autism spectrum disorder (ASD) persisting after transition to adulthood. The Program for the Education and Enrichment of Relational Skills for Young Adults (PEERS®-YA) is an evidence-based intervention found to be effective in improving relational skills in young adults with ASD. To translate the original American version of the PEERS®-YA treatment manual into Korean, intensive interviews were performed. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, individuals with ASD who are more aware of their problems may experience severe mental health symptoms. Studies applying PEERS ® to individuals with ASD and high levels of functioning have confirmed improved social function and mental health symptoms [ 4 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, individuals with ASD who are more aware of their problems may experience severe mental health symptoms. Studies applying PEERS ® to individuals with ASD and high levels of functioning have confirmed improved social function and mental health symptoms [ 4 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed the data of parents who participated in an RCT of the PEERS ® -YA-K [ 5 ]. Among the 64 participants, 23 mothers and 4 fathers participated as social coaches.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching ecologically effective skills to nurture and maintain friendships using psycho-educational and cognitive-behavioral therapy techniques ( 35 ). PEERS training has been successively introduced and updated locally in Korea ( 36 ), Japan ( 37 ), Israel ( 38 ), the Netherlands ( 39 ), and Hong Kong ( 40 ), with good results in local ASD patients ( 41 ). Patients with ASD are often accompanied by depression, anxiety, intellectual disability, attention deficit, and other psychiatric comorbidities.…”
Section: Introductionmentioning
confidence: 99%